6c+11=-55-5c

Simple and best practice solution for 6c+11=-55-5c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6c+11=-55-5c equation:


Simplifying
6c + 11 = -55 + -5c

Reorder the terms:
11 + 6c = -55 + -5c

Solving
11 + 6c = -55 + -5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '5c' to each side of the equation.
11 + 6c + 5c = -55 + -5c + 5c

Combine like terms: 6c + 5c = 11c
11 + 11c = -55 + -5c + 5c

Combine like terms: -5c + 5c = 0
11 + 11c = -55 + 0
11 + 11c = -55

Add '-11' to each side of the equation.
11 + -11 + 11c = -55 + -11

Combine like terms: 11 + -11 = 0
0 + 11c = -55 + -11
11c = -55 + -11

Combine like terms: -55 + -11 = -66
11c = -66

Divide each side by '11'.
c = -6

Simplifying
c = -6

See similar equations:

| (9+8x^2+9x^2-7x^2)+(-2x^3+2x^2+2+5x^4)= | | 11x-1=7x+8 | | 3e-5x=132 | | -16x^2+26x=0 | | 30=4x+16 | | 7k-13k+10k-3k=20 | | 7+8c=21+c | | 18c-17c=20 | | 3c-5=10c-26 | | -8x+4=4x | | 4t-2t-t+3t+2t=18 | | 2k=50 | | 5v-5v+2v=10 | | y=3+-5x | | 7w-3(2w+4)=11 | | x^3-k^2x=0 | | 9h+5=95 | | 4w-4w+2w-w=19 | | 3c+21=10c-63 | | 7m-30=26 | | 200=4m | | 18x-(8x-7)=57 | | -(2k+11)=7 | | 2x^2+11x=4x+49 | | 20=15+y | | 15w+2w-7w-9w=11 | | bc+3g=2kforc | | 0=2(x+7)(x-1) | | 9(-1)+11-6(-1)=17 | | 14x+15=7x+48 | | g(x)=-logx-6 | | 12x^2+24x-12=0 |

Equations solver categories